(untitled) (Eurasian Journal of Ecology, 2016)
At inspection of small steppe reservoirs of the West Kazakhstan area, the zooplankton was characterized by rather high variety (45 таксонов). Its basis (76 %) was formed by crustaceans of four groups - Cladocera, Copepoda, Anostraca, Conchostraca. The minimum number of kinds is revealed in a zooplankton of reservoirs - of the "cubes " having very low transparency of water. In these reservoirs two Kazakhstan of a kind new to fauna веслоногих island Calanoida - Arctodiaptomus ulomskyi Chechura and A are found out. spinosus (Daday).